Persepsi Peserta Didik Kelas XI IPS Man Kota Singkawang Terhadap Situs Sejarah Pemerintah Kolonial Belanda di Singkawang - Anisya Fitrianti; Aminuyati Aminuyati; Astrini Eka Putri (Peneliti.net, 2023)
The purpose of this study was to find out information about the perceptions of class XI IPS MAN Singkawang students towards historical sites of the Dutch colonial government in Singkawang. The research method used in this study uses descriptive qualitative research methods. Research subjects consist of 3 classes namely class XI IPS 1, XI IPS 2, and XI IPS 3. Researchers conducted interviews, observations, and documentation in the data collection method stage. Then perform data analysis techniques through the steps of data collection, data presentation, data reduction, and drawing conclusions as well as data verification. In increasing students' understanding of the Dutch colonial government sites in Singkawang City. The teacher's efforts have been to deliver local history material on historical sites of the Dutch colonial government in Singkawang to students in class XI IPS 1, XI IPS 2, and XI IPS 3 and give assignments to report to students to visit historical sites of the Dutch colonial government in Singkawang. The results showed that the use of historical sites of the Dutch colonial government in Singkawang in history subject matter at school could be used as a source of local history learning, making students enthusiastic about learning history, because they could see evidence of historical relics or historical sites of the Dutch colonial government in Singkawang. add insight into local history to students, who lack knowledge of local history in the area. Adding to the curiosity of students, which adds local material to history learning material in schools can attract the attention of students in learning history.